Analisis Miskonsepsi Calon Guru IPA pada Lima Konsep Dasar Sains Menggunakan Tes Diagnostik Three-Tier - Khoriyah, Fara Ainul; Nadhif, Muhammad Yusron; Aliyah, Himmatul; Labib, Muchsin; Aliah, Siti; Prasetyo, Dody Rahayu (STKIP HARAPAN BIMA, 2025)
This study aims to identify misconceptions among prospective science teachers regarding five basic science concepts, namely force and motion, energy and its transformations, heat and its transfer, simple electricity, and photosynthesis, using the Three-Tier Diagnostic Test instrument. The research method used is quantitative descriptive with a diagnostic survey conducted on 20 second-semester students from the Science Education program at IAIN Kudus. The results indicate a high level of misconceptions in all concepts, with the highest percentage found in the concepts of force and motion (56.0%) and energy and its transformations (57.1%). These findings suggest a lack of proper conceptual understanding among prospective teachers, which may affect the science learning process. The use of the Three-Tier Diagnostic Test has proven effective in distinguishing misconceptions from ignorance. Therefore, it is recommended to develop interactive learning methods and periodic evaluations to address misconceptions and improve the mastery of science concepts among prospective teachers.